Entrenamiento en estrategias para modificar distorsiones cognitivas en mujeres maltratadas por su pareja con edades comprendidas entre los 18-35 años de edad, que acuden al Centro de Equidad y Justicia Quitumbe, durante los meses de mayo a septiembre de 2015 - Caiza Ortiz, Evelyn Elizabeth (2016)
This research project is about psychological intervention for female victims of violence by their intimate partner through the modification of cognitive distortions. The emergence of these erroneous thoughts causes a distortion in their perception of, others and themselves. The objective of this study was cognitive restructuring of erroneous thoughts arising in the group of participants in order to reduce their emotional distress and improves their emotional, psychological, social and employment aspects. This group was made up of women who participated voluntarily in this project throughout the process. A total of fifteen workshops were made once a week. In each of them different tools and activities were used. After finishing the project an evaluation was made. The evaluation showed statistically significant changes in modifying nine cognitive distortions, which contributed to the reaffirmation of their self-confidence and a significant reduction in emotional distress, and demonstrated that they had learned in a complementary way to solve problems and make assertive decisions. When the project was finished, it showed efficiency in the application of this model of psychological intervention, recommending its use in the future.